Proteção à autoria e combate ao plágio acadêmico na FAINOR: referenciais didáticos instrucionais. - Soares, Ronaldo (2014)
The systematic combat plagiarism is a major concern in academia today. Among the reasons for the practice of plagiarism in academic work can mention the ease in obtaining jobs and information on various topics and areas of knowledge , lack of time for research and writing , the lack of knowledge of relevant legislation and ignorance of the rules of quotes . Several studies on the topic have been developed and published , and educational institutions have been focusing their combat, is raising awareness of the importance of reducing their practice , whether through adoption of severe penalties institutional measures and also the orientation researchers how to do citations and references in accordance with the technical standards imposed . The purpose of this manual is to promote systematization of institutional policies on the Northeast Independent School ( FAINOR ) , so that students , teachers and researchers become aware of the importance of minimizing the practice of plagiarism at the institution , and present a set of combat actions which could significantly reduce its impact on academic papers.